Dynamics and weed control effectiveness of dicamba herbicide when applied directly on the soil and corn straw in Brazil - Mundt, Tamara Thaís [UNESP]; Carbonari, Caio Antonio [UNESP]; Moisinho, Ivana Santos [UNESP]; de Brito, Ivana Paula Ferraz Santos [UNESP]; Picoli Junior, Gilmar José; Ovejero, Ramiro Fernando Lopez; Velini, Edivaldo Domingues [UNESP] (Taylor & Francis, 2022)
Dicamba is a post-emergence herbicide commonly used to control broadleaves in cereal crops. However, a portion of the herbicide might reach soil surface, and many factors could affect its dynamics and effects. The objective of this research was to evaluate the dynamics of dicamba applied to the soil, to the soil and covered with straw and over the straw, in addition, to evaluate the weed control in pre-emergence. Two field experiments at different locations were conducted with dicamba. To quantify dicamba in the soil a LC-MS/MS system was used. In both experiments, rainfall and straw played a key role in dicamba soil dynamics and weed control. Dicamba in the soil was affected by presence of straw and accumulated rainfall after the application. Higher concentrations (254–432 ng g soil−1) in the soil 0–10 cm layers and greater leaching potential were found for the application in the soil compared to over the straw. The maximum concentration of dicamba (101.6–226 ng g soil−1) was found after 10 mm of rainfall for dicamba application over the straw. Around 60–70% of weeds were controlled with concentrations greater than 20 ng/g soil−1, in the presence or absence of straw.
Keywords: LCMSMS; no-till system; Synthetic auxin herbicides; weed control